2021
DOI: 10.1108/prr-07-2021-0033
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of student with disability living in off-campus student housing in Ghana: a Gap Model approach

Abstract: PurposePrevious students' housing studies have neglected the need to study all-inclusive student housing and quality of services delivery among students with disability. This study explores the expectations in students' housing among university students living with disabilities (SWDs) in Ghana.Design/methodology/approachThe study adopted a mixed-methods approach, involving 423 SWD selected from five public and three private universities across Ghana. Grounded on the Gap Model, the study employed exploratory fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 29 publications
2
29
1
Order By: Relevance
“…In the Ghanaian context, student housing has become relevant among tertiary educational institutions because of the central government and developers' low capacity and inability to adequately accommodate the increasing student population (Attakora-amaniampong et al, 2020). As part of the growing nature of student housing across developing countries, studies have confirmed that student housing investors have focused on students' preferences such as accessibility and proximity, comfort, entertainment and security as means of increasing student turn-out and returns (Attakora-Amaniampong et al, 2021;Khajehzadeh and Vale, 2016;Sanni-anibire and Hassanain, 2016). However, implementing innovations to increase occupancy and sustain investment returns among student housing investment options is emerging around university campuses (French et al, 2018).…”
Section: Student Housingmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Ghanaian context, student housing has become relevant among tertiary educational institutions because of the central government and developers' low capacity and inability to adequately accommodate the increasing student population (Attakora-amaniampong et al, 2020). As part of the growing nature of student housing across developing countries, studies have confirmed that student housing investors have focused on students' preferences such as accessibility and proximity, comfort, entertainment and security as means of increasing student turn-out and returns (Attakora-Amaniampong et al, 2021;Khajehzadeh and Vale, 2016;Sanni-anibire and Hassanain, 2016). However, implementing innovations to increase occupancy and sustain investment returns among student housing investment options is emerging around university campuses (French et al, 2018).…”
Section: Student Housingmentioning
confidence: 99%
“…, 2020). As part of the growing nature of student housing across developing countries, studies have confirmed that student housing investors have focused on students' preferences such as accessibility and proximity, comfort, entertainment and security as means of increasing student turn-out and returns (Attakora-Amaniampong et al. , 2021; Khajehzadeh and Vale, 2016; Sanni-anibire and Hassanain, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…With the ongoing reflections, architectural designs and space usage for crowded populations have become more essential to be scrutinized. Housing is perceived as one of the physiological, psychological and social needs required for the quality existence of students, which has a bearing on the development of the human capital of every nation (Attakora-Amaniampong et al, 2021;Nazarpour and Norouzian-maleki, 2021). However, university campuses are looking to return to normal in the COVID-19 pandemic (Yıldırım et al, 2021).…”
mentioning
confidence: 99%